"Be Soft": Irony, Postfeminism, and Masculine Positions in Swedish Sport Betting Commercials. (December 2021) - Goedecke, Klara
Gambling advertising usually draws heavily on gendered stereotypes, including portrayals of male gamblers as tough and successful. Meanwhile, representations of men in advertising have grown increasingly diverse, with emotional and sexualized men accompanying heroic, muscular portrayals. In this article, both these bodies of research are drawn upon to discuss a series of Swedish sports betting commercials which encourage the viewer to "bet hard" while also "being soft." The celebration of "softness" is ambiguous but can be seen as referencing gendered, political discussions about men and masculinity. Engaging with hybrid masculinities theory, postfeminism, and discourses about gambling and betting, the article demonstrates that meanings around "softness" are ambiguous, ironic, and serve to normalize gambling by distancing it from discourses about addiction. The commercials represent a shift in gambling advertising, but the linking of men's politics to gambling also represents a new complexity in narratives about "new, " or "soft, " men.